2016
DOI: 10.1007/s11663-016-0700-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Cause of Spontaneous Emulsification of a Free Steel Droplet; Validation of the Chemical Exchange Pathway

Abstract: Small Fe-based droplets have been heated to a molten phase suspended within a slag medium to replicate a partial environment within the basic oxygen furnace (BOF). The confocal scanning laser microscope (CSLM) has been used as a heating platform to interrogate the effect of impurities and their transfer across the metal/slag interface, on the emulsification of the droplet into the slag medium. The samples were then examined through X-ray computer tomography (XCT) giving the mapping of emulsion dispersion in 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Secondly the reported decarburization rate is from a static laboratory test where a quiescent gas halo is able to form and diffusion across this halo is likely rate limiting, this is unlikely to be the case in the industrial setting of converter decarburization when mass flow of material in the emulsion phase will disrupt a significant gas boundary forming, meaning ion mass transfer in the slag is more likely rate limiting. Given recent findings reported by Assis 29) and Spooner,30) where droplets are seen to spontaneously emulsify and the extreme increase in surface area this invokes, high values of emulsification contribution are possible. This would allow significantly higher decarburization rates, as such the above calculation does not take into account the morphology of detected droplets; spherical droplets are assumed.…”
Section: Evaluation Of Assumptionsmentioning
confidence: 85%
“…Secondly the reported decarburization rate is from a static laboratory test where a quiescent gas halo is able to form and diffusion across this halo is likely rate limiting, this is unlikely to be the case in the industrial setting of converter decarburization when mass flow of material in the emulsion phase will disrupt a significant gas boundary forming, meaning ion mass transfer in the slag is more likely rate limiting. Given recent findings reported by Assis 29) and Spooner,30) where droplets are seen to spontaneously emulsify and the extreme increase in surface area this invokes, high values of emulsification contribution are possible. This would allow significantly higher decarburization rates, as such the above calculation does not take into account the morphology of detected droplets; spherical droplets are assumed.…”
Section: Evaluation Of Assumptionsmentioning
confidence: 85%
“…In addition, the present authors have explored droplet reactions under non-gas-producing conditions and have observed the phenomenon of spontaneous emulsification. [70][71][72][73][74] Small pucks (approximately 17 mg) of electrically pure iron with < 34 ppm oxygen were loaded in the center of 8-mm-OD MgO crucibles surrounded by a slag with composition similar to that seen at the end of BOF processing. The most notable reactant in the slag phase was the 36 pct FeO content.…”
Section: Behavior Of Metal Droplets In the Bofmentioning
confidence: 99%
“…Due to the heating method, the small size of the sample, and the cold environment within the furnace, these samples are reliably frozen in a state similar to those at high temperatures. The application of XCT as a nondestructive technique allows the imaging of the droplets without sectioning or milling, methods which would destroy the complex geometries the droplets uptake, as seen in Figure 1: [71]…”
Section: Behavior Of Metal Droplets In the Bofmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies on dephosphorization kinetics and phosphorus partition between liquid iron and oxidizing slag have been carried out by Manning et al, Assis et al, and Yang et al More recently, reviewing published phosphorus partition equations, Drain et al developed a new phosphorus partition correlation based on industrial data, which can be used in basic oxygen steelmaking conditions. Several very interesting investigations, on the emulsification behavior due to material exchange between liquid metal and molten oxide, have been conducted by Assis et al and Spooner et al using high temperature confocal scanning laser microscopy and micro X‐ray computer tomography (XCT). While these workers studied conditions which were not entirely relevant to the current work their observations offer some potential points of comparison.…”
Section: Introductionmentioning
confidence: 99%